UTILIZING CHATGPT IN ENGLISH LANGUAGE LEARNING AT DONG NAI TECHNOLOGY UNIVERSITY: PERSPECTIVES, ATTITUDES AND CHALLENGES FACED BY EFL STUDENTS - Phan Thi Lam*, Nguyen Thi Dieu Huyen (Tạp chí Khoa học)
This study investigates the incorporation of ChatGPT in English as a Foreign Language (EFL) instruction at Dong Nai Technology University, emphasizing students' attitudes, perceptions, and obstacles. A mixed-method approach was utilized, comprising 120 students majoring in English who participated in the study. Data were gathered via structured questionnaires and semi-structured interviews. The results demonstrate that students have positive attitudes toward ChatGPT, which helps students enhance writing proficiency, grammar, and vocabulary development. However, apprehensions about correctness, excessive dependence, and restricted interactivity remain. The research underscores the advantages and constraints of AI-assisted learning and provides suggestions for its effective integration into EFL instruction.